CRISPR library screening to develop HEK293-derived cell lines with improved lentiviral vector titers - Iaffaldano, Brian J.; Marino, Michael P.; Reiser, Jakob (Frontiers in Genome Editing, 2023)
Lentiviral (LV) vectors have emerged as powerful tools for treating genetic and acquired human diseases. As clinical studies and commercial demands have progressed, there has been a growing need for large amounts of purified LV vectors. To help meet this demand, we developed CRISPR library screening methods to identify genetic perturbations in human embryonic kidney 293 (HEK293) cells and their derivatives that may increase LV vector titers. Briefly, LV vector-based Human CRISPR Activation and Knockout libraries (Calabrese and Brunello) were used to modify HEK293 and HEK293T cells. These cell populations were then expanded, and integrated LV vector genomes were rescued by transfection. LV vectors were harvested, and the process of sequential transduction and rescue-transfection was iterated. Through this workflow, guide RNAs (gRNAs) that target genes that may suppress or enhance LV vector production were enriched and identified with Next-Generation Sequencing (NGS). Though more work is needed to test genes identified in this screen, we expect that perturbations of genes we identified here, such as TTLL12, which is an inhibitor of antiviral innate immunity may be introduced and multiplexed to yield cell lines with improved LV vector productivity.